Measuring the Spillovers of Venture Capital - Monika Schnitzer; Martin Watzinger (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
We provide the first measurement of knowledge spillovers from venture capital-financed companies onto the patenting activities of other companies. On average, these spillovers are nine times larger than those generated by the R&D investment of established companies. Spillover effects are larger in complex product industries than in discrete product industries. Start-ups with experienced inventors holding a patent at the time of receiving the first round of investment produce the largest spillovers, indicating that venture capital fosters the commercialization of technologies. Methodologically, we contribute by developing a novel definition of the spillover pool, combining citation-based and technological proximity-based approaches.
Keywords: G24; O30; O31; O32; 330; venture capital; spillovers; innovation